A STUDY OF NARCISSISM AMONG THE BUSINESS STUDENTS AND INDUSTRIAL ENGINEERING STUDENTS - Hapsari, Nadia Athinna; Pratama, Andika Putra (Journal of Business and Management, 2018)
Abstract. As one of the top universities in Indonesia, Intitut Teknologi Bandung is expected to produce graduates who are competent, with qualified skills. As previously mentioned by Satrio Madigondo, a head hunter who had observed the personality trends in ITB graduates for four years, he assumed the ITB graduates he ever met were having a high tendency towards narcissism compared to the other graduates from two other top universities in Indonesia such as Universitas Indonesia and Universitas Gadjah Mada (http://thriea.blogspot.com/2012/01/kata-mereka-tentang-itb.html?m=1). He also added that it is quite striking and disrupting the recruitment process. This research aims to become one of the more explicit studies on narcissism levels among students in Institut Teknologi Bandung and also to analyze whether narcissism reflects their career expectations in the future. There are four aspects of narcisism, Exploitativeness / Entitlement, Leadership / Authority, Superiority / Arrogance, and Self-Absorption / Self-Admiration, as for the indicators of career expectations, they are ease of finding a job, income expectations, and promotion expecations. This research sampled students of business and industrial engineering. Based on the previous research , it is found that narcissistic tendencies such as materialistic values and money importance tend to be enhanced in business students (e.g., Robak et al., 2007; Vansteenskiste, Duriez, Simons, & Soenens, 2006) and the sampling of industrial engineering students seem particularly relevant since business school grew out of the Department of Industrial Engineering. A quantitative approach was applied by spreading online questionnaire to business and industrial engineering students in Institut Teknologi Bandung. Overall, 445 were collected. The datas were assessed using Independent Sample T-Test, One Way Analysis of Variance (ANOVA), Two Way Analysis of Variance (ANOVA), and Multivariate Analysis Covariance (MANCOVA). The findings revealed that the business students in Institut Teknologi Bandung have significantly higher levels of narcissism compared to industrial engineering students, even after controlling for gender and place of origin. Further narcissism related to higher expectations toward future career.Keywords : business, career, higher education, industrial engineering, narcissismÂ